Accounting for Research Induced Environmental Impacts Using Life Cycle Assessment - Cooney, Ronan; Tahar, Alexandre; Kennedy, Alan; Clifford, Eoghan (Frontiers in Sustainability, 2021)
Since the 1970’s the number of scientific publications with sustainability as a keyword has increased from 1 in 1975 to 13,628 in 2019. Research, like all human endeavours, has impacts on the environment due to the activities required to generate the supporting data (i.e. use of vehicles, resources and materials). Researchers have a responsibility to minimise their impacts as part of their work and to make environmentally responsible decisions. A life-cycle approach is currently the best-developed means of assessing the impact of a group or organisation. This article presents a case study of organisational life cycle assessment (O-LCA) of a research project. The objectives of this study were to (i) estimate the impact of the project, focusing on travel. (ii) Use a post hoc approach to determine impact reduction opportunities. (iii) Apply O-LCA as a decision-making tool in project management of research and (iv) profile the environmental impact of the project using public data (manufacturers figures) and proprietary datasets. The results of this study indicate that the greatest impact arising from the project was due to commuting followed by conference and training attendance, fieldwork and meetings. Scenarios modelling, alternative vehicle use, flexible working arrangements and stakeholder events highlighted the reduction potential that could have been implemented as part of the project. O-LCA proved to be an appropriate tool for assessing the impact of a research group and that it has the potential to inform decisions and management of academic projects and events. It should be noted that the ability of research groups or personnel to bring about change might be limited, typically due to their placement within a larger organisation (e.g. a higher education institute). The recent COVID-19 pandemic, has hastened the shift to remote working practices for many organisations. Recent surveys indicate that more than 80% of respondents would like to work remotely, at least some of the time, after the pandemic. This modal shift in working practices offers an immediate opportunity for environmental relief. It is recommended that O-LCA be incorporated into groups and organisations to support their decision-making practices to foster responsible and sustainable research.